2021
DOI: 10.1002/anie.202013987
|View full text |Cite
|
Sign up to set email alerts
|

An ER‐Targeting Iridium(III) Complex That Induces Immunogenic Cell Death in Non‐Small‐Cell Lung Cancer

Abstract: Immunogenic cell death (ICD) is a vital component of therapeutically induced anti‐tumor immunity. An iridium(III) complex (Ir1), containing an N,N‐bis(2‐chloroethyl)‐azane derivate, as an endoplasmic reticulum‐localized ICD inducer for non‐small cell lung cancer (NSCLC) is reported. The characteristic discharge of damage‐associated molecular patterns (DAMPs), that is, cell surface exposure of calreticulin (CRT), extracellular exclusion of high mobility group box 1 (HMGB1), and ATP, were generated by Ir1 in A54… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
104
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(105 citation statements)
references
References 73 publications
0
104
0
1
Order By: Relevance
“…Immunogenic cell death (ICD) is a form of cell death in which ICD occurs in tumor cells; a series of signaling molecules are involved, including the release of calreticulin (CRT), heat-shock protein (HSP70), adenosine triphosphate (ATP) and high mobility group box 1 (HMGB1) [ 41 ]. ICD is believed to overcome drug resistance caused by tumor, enhance antitumor immunity, and achieve better therapeutic effect [ 63 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunogenic cell death (ICD) is a form of cell death in which ICD occurs in tumor cells; a series of signaling molecules are involved, including the release of calreticulin (CRT), heat-shock protein (HSP70), adenosine triphosphate (ATP) and high mobility group box 1 (HMGB1) [ 41 ]. ICD is believed to overcome drug resistance caused by tumor, enhance antitumor immunity, and achieve better therapeutic effect [ 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…Next, the secondary antibody FITC-labeled Goat Anti-Rabbit IgG was incubated in darkness for 1 h. The cells were washed three times with PBS. Finally, the nuclei were stained with Hoechst and photographed under Micro XLS System (MD company, San Jose, CA, USA) [ 41 ].…”
Section: Methodsmentioning
confidence: 99%
“…Accumulating studies have combined nanoparticles with immunoadjuvants, chemotherapeutics, photodynamic therapy, or again photothermal therapy in order to reshape the tumor hypoxic microenvironment to elicit or enhance ICD (81,82). These novel nanoparticles synergized with IR and enhanced antitumor immune function (83)(84)(85)(86)(87). Qian Chen et al confirmed that PLGA-R837@Cat nanoparticle-based x-ray radiation inhibited primary tumors significantly in comparison with RT alone.…”
Section: The Methods Of Enhancing Ir-induced Icdmentioning
confidence: 99%
“…Hence, it is desirable to develop PSs that could target organelles and generate high dosage of 1 O 2 in situ to directly cause dysfunction of subcellular organelles and activate specific cell death signals. Several PSs targeting mitochondria 15 17 , endoplasmic reticulum (ER) 18 20 , lysosome 21 , 22 and cell membrane 23 , 24 have been reported and exhibited high PDT efficiency. However, due to the lack of effective Golgi apparatus (GA) targeting strategies, specific GA targeting AIEgen-based PSs have seldom been reported.…”
Section: Introductionmentioning
confidence: 99%